Advancing Retail Operations: A Customizable IoT-Based Smart Inventory System - Chai, Tong-Yuen; Haw, Su Cheng; Jahangir, Muhammad; Hoe, Kwan Ban; Heng, Lim Ean; Vellaisamy, Muthukumar (International Journal of Membrane Science and Technology, 2023)
The retail sector has encountered formidable challenges in recent years, particularly concerning food sustainability and the need for reduced manpower, which have been further exacerbated by the COVID-19 pandemic. The inventory management process involves critical tasks such as environment checking, product inspection, and stock arrangement, all of which are essential for maintaining product quality. Price label management is another crucial aspect of retail operations, providing key information to potential customers. However, the labor-intensive process of installing and replacing price labels, as well as adapting to market trends, poses efficiency and sustainability concerns. To address the aforementioned challenges, we have proposed an IoT-based inventory management system that consists of three interconnected components: a smart shelf that keeps real-time track of humidity, temperature, and air index; electronic shelf labeling that allows for easy updating of product information from mobile/PC devices; and RFID-based stock sorting to track product in/out and location. Hence, the proposed integrated solution significantly enhances operational efficiency, reduces overall workload, optimizes inventory management tasks, streamlines operations, and mitigates financial losses associated with inefficient processes.